Rancang Bangun Alat Pendeteksi Hidrasi Tubuh Dan Kadar PH Urine Berbasis IOT (Internet Of Things) - Desak Ketut Sutiari; Titi Meta; Aryani Adami (Ikatan Cendekiawan Hindu Indonesia Regional Sulawesi Tenggara, 2025)
Urine is an excretory product produced by the kidneys and then excreted from the body through the urinalysis process. Detection of hydration from urine can be seen by looking at the color of urine, clarity and volume of urine when urinating. In this era of technology, it is becoming more sophisticated and faster so that the time used is more effective. One of the current technological developments is the Internet of Things, namely monitoring several devices or equipment that can be accessed via smartphone or personal computer. The aim of this research is to design and create an IoT-based device for detecting body hydration and urine pH levels. This design uses 3 main components, namely NodeMCU ESP32, photodiode sensor and pH sensor. NodeMCU ESP32 is a microcontroller that will communicate serially so that it is more practical to use. Photodiode sensor to determine the level of urine turbidity. pH sensor to detect the normality of a person's body pH. An IoT-based device for detecting body hydration and urine pH levels has been successfully created. Based on urine pH measurements, a difference of 0.25 was obtained compared to a calibrated pH meter with an error value of 4.25%. Measuring turbidity levels using a photodiode sensor has a fairly good level of accuracy. This IoT-based tool for detecting body hydration and urine pH levels can make it easier for users to monitor measurement results remotely. Communication between remote devices is greatly influenced by the availability of the internet and applications on smartphones and devices. In the IoT system, the NodeMCU and smartphone must use the WiFi network that has been uploaded to the NodeMCU ESP32. In order to develop further research, it can be done by adding a larger LCD and adding a memory card as a data storage location.